Particulate matter combustion. Cordierite-supported potassium nitrate catalysts modified with transition metal oxides - Leguizamón Aparicio, María Silvia del Valle (2019)
In this work, cordierite-supported potassium nitrate catalysts modified with transition metal oxides are studied as catalysts for the particulate matter combustion from diesel engine emissions. The catalysts were prepared by nitrate solutions. The catalysts were characterized by XRD, differential scanning calorimetry (DSC), thermal programmed reduction (TPR), vibrational spectroscopy (FTIR) and Scanning microscopy provided with EDS analyzer. KNO3 containing catalysts present high activity in the presence of O2/NO. The Tmax obtained with these catalysts decreases more than 200ºC with respect to the temperature of the non-catalyzed process. The activity is associated with the presence of KNO3 and the role of this salt can be attributed to the NO3-/ NO2- redox cycle contribution and to the surface wetting effect.